A Contact Line Dynamic Model for a Conducting Water Drop on an Electrowetting Device (Communications in Computational Physics, 2018)
The static shape of drop under electrowetting actuation is well studied andrecent electrowetting theory and experiments confirm that the local contact angle (microscopicangle) is unaffected while the apparent contact angle (macroscopic angle) ischaracterized by the Lippmann-Young equation. On the other hand, the evolution ofthe drop motion under electrowetting actuation has received less attention. In this paper,we investigate the motion of a conducting water drop on an electrowetting device(EWD) using the level set method. We derive a contact line two-phase flow modelunder electrowetting actuation using energy dissipation by generalizing an existingcontact line model without the electric field. Our model is consistent with the staticelectrowetting theory as the dynamic contact angle satisfies the static Young's equationunder equilibrium conditions. Our steady state results show that the apparentcontact angle predicted by our model satisfies the Lippmann-Young's relation. Ournumerical results based on the drop maximum deformation agree with experimentalobservations and static electrowetting theory. Finally, we show that for drop motionour results are not as good due to the difficulty of computing singular electric field accurately.Nonetheless, they provide useful insights and a meaningful first step towardsthe understanding of the drop dynamics under electrowetting actuation.